Data from: Consequences of repeated sarcoptic mange outbreaks in an endangered mammal population - Wallén, Johan; Erlandsson, Rasmus; Larm, Malin; Meijer, Tomas; Noren, Karin; Angerbjörn, Anders (Zenodo, 2024)
Diseases and parasites are important drivers of population dynamics in wild mammal populations. Small and endangered populations that overlap with larger, reservoir populations are particularly vulnerable to diseases and parasites, especially in ecosystems highly influenced by climate change. Sarcoptic mange, caused by a parasitic mite (Sarcoptes scabiei), constitutes a severe threat to many wildlife populations and is today considered a panzootic. The Scandinavian arctic fox (Vulpes lagopus) is endangered with a fragmented distribution and is threatened by e.g., red fox (Vulpes vulpes) expansion, prey scarcity and inbreeding depression. Moreover, one of the subpopulations in Scandinavia has suffered from repeated outbreaks of sarcoptic mange during the past decade, most likely spread by red foxes. This was first documented in 2013 and then again 2014, 2017, 2019, 2020 and 2021. We used field inventories and wildlife cameras to follow the development of sarcoptic mange outbreaks in this arctic fox subpopulation with specific focus on disease transmission and consequences for reproductive output. In 2013-14, we documented visual symptoms of sarcoptic mange in about 30% of the total population. Despite medical treatment, we demonstrate demographic consequences where the number of arctic fox litters plateaued and litter size was reduced after the introduction of S. scaibei. Furthermore, we found indications that mange likely was transmitted by a few arctic foxes travelling between several dens, i.e., "super-spreaders". This study highlights sarcoptic mange as a severe threat to small populations and can put the persistence of the entire Scandinavian arctic fox population at risk. Funding provided by: Swedish Research Council for Environment Agricultural Sciences and Spatial Planning ROR ID: https://ror.org/03pjs1y45 Award Number: 2013-01856 Funding provided by: EU-LIFE* Crossref Funder Registry ID: Award Number: SEFALO and SEFALO+ Funding provided by: EU Interreg* Crossref Funder Registry ID: Award Number: Felles ...